Studi Model Pembelajaran Pendidikan Sejarah - Muhammad Fendi Aditya (Journal on Education, 2023)
The purpose of this study is to investigate the policies of the principal at SMA Negeri 4 Magelang regarding History subjects, the curriculum policies regarding the placement portion of History subjects, how teachers convey material and learning models of History at SMA Negeri 4 Magelang, and how students think about the teacher delivers historical material. This study used a qualitative descriptive methodology, involving classroom observations, interviews with school principals and vice principals for curriculum, and history teachers, and distributing questionnaires to students. The SMA Negeri 4 Magelang school uses the 2006 curriculum and promotes the instillation of noble values, with a focus on multicultural values and religious values. History is one of the mainstay subjects. The research conducted at this school found that the history subject is interesting to students because the teachers are creative and innovative, and this subject is used as a means of knowledge transfer.